Project Management Rescues Healthcare.gov: A PMBOK-Inspired Analysis of Overcoming IT Project Challenges - Ambo, Nur Afizah Nazatul; Iman Sofia,; Siti Zulalina,; Afiq Haikal,; Raffael Lawrenzier,; Yacqub Isse,; Ibrahim Asim,; Abobkr Eisa,; Siti Hajar Arbain, (Applied Information Technology And Computer Science, 2023)
The launch of the Healthcare.gov website in 2013 served as an interesting case study that demonstrated the practical application of project management principles in the face of unexpected IT project issues. This article discusses challenges faced during website launches, including performance and stability issues, and how project managers leverage the Project Management Body of Knowledge (PMBOK) to manage and resolve these challenges. Project managers effectively use PMBOK key knowledge areas, such as Integration, Scope, Risk, Quality and Communication Management, to navigate these complex situations. Their responses include integrated change control, tight scope management, risk assessment and mitigation, an emphasis on quality assurance, and transparent communication with stakeholders. This case study highlights the important role of project management in saving high-stakes projects and provides valuable insights into managing IT project incidents.